2021
DOI: 10.1080/21655979.2021.2003664
|View full text |Cite
|
Sign up to set email alerts
|

Ring finger 220 promotes the stemness and progression of colon cancer cells via Ubiquitin specific peptidase 22-BMI1 axis

Abstract: Colorectal cancer (CRC) is ranked as the third most common malignancy worldwide. Therefore, it is urgent to screen novel and effective molecular drug targets for colorectal cancer therapeutics. In this study, the specific role and related mechanism underlying Ring finger (RNF) 220 in colon cancer were investigated. Firstly, RT-PCR assay was used to compare differences between expression levels of RNF220 in colorectal tumor and normal tissues. Western blot and RT-PCR assays were applied to examine the protein l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…At their N-terminus, RING finger proteins have a RING structural domain that interacts with ubiquitin and transports it to the protein substrate. RNF proteins play a function in the growth of various cancers [ 33 ]. For example, RNF126 is linked to early breast cancer metastasis and promotes breast cancer cell proliferation and development [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…At their N-terminus, RING finger proteins have a RING structural domain that interacts with ubiquitin and transports it to the protein substrate. RNF proteins play a function in the growth of various cancers [ 33 ]. For example, RNF126 is linked to early breast cancer metastasis and promotes breast cancer cell proliferation and development [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that RNF2 expression is signi cantly increased in tumour cells of gastric cancer patients, and knockdown of RNF2 inhibits tumour cell viability by affecting the cell cycle 34 . In both in vivo and in vitro experiments, it was discovered that RNF220 is signi cantly upregulated in colorectal cancer 35 . Furthermore, cell scratch and plate clone formation experiments demonstrated that RNF220 promotes the proliferation, migration, and invasion of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cell scratch and plate clone formation experiments demonstrated that RNF220 promotes the proliferation, migration, and invasion of colorectal cancer cells. Subsequently, a subcutaneous xenograft tumour mouse model was established, which revealed that RNF220 promotes tumour growth in vivo 35 . This upregulation promoted invasion and metastasis of both types of cancer cells by increasing the epithelial mesenchyme.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that ring finger 220 (RNF220) is upregulated in CRC tissues and cell lines and is associated with increased CRC stemness and tumor growth in vivo . This oncogenic activity of RNF220 is indirectly mediated by USP22[ 49 ]. USP22 also stabilizes ZRANB1 (zinc finger RANBP2-type containing 1), a positive regulator of the Wnt/β-catenin pathway, and promotes SC-like features of CRC cells[ 50 ].…”
Section: Discussionmentioning
confidence: 99%